Anti-amnesic effect of extract and alkaloid fraction from aerial parts of Peganum harmala on scopolamine-induced memory deficits in mice. (23rd May 2017) - Liu, Wei; Zhu, Yudan; Wang, Yongli; Qi, Shenglan; Wang, Yuwen; Ma, Chao; Li, Shuping; Jiang, Bo; Cheng, Xuemei; Wang, Zhengtao; Xuan, Zhenyu; Wang, Changhong
Abstract: Ethnopharmacological relevance: Aerial parts of Peganum harmala Linn (APP) is used as traditional medical herb for treatment of forgetfulness in Uighur medicine in China. But, the active ingredients and underlying mechanisms are unclear. Aim of the study: The present study was undertaken to investigate the improvement effects of extract and alkaloid fraction from APP on scopolamine-induced cognitive dysfunction and to elucidate their underlying mechanisms of action, and to support its folk use with scientific evidence, and lay a foundation for its further researches. Materials and methods: The acetylcholinesterase (AChE) inhibitory activities of extract (EXT), alkaloid fraction (ALK) and flavonoid fraction (FLA) from APP were evaluated in normal male C57BL/6 mice. The anti-amnesic effects of EXT and ALK from APP were measured in scopolamine-induced memory deficits mice by the Morris water maze (MWM) tasks. The levels of biomarkers, enzyme activity and protein expression of cholinergic system were determined in brain tissues. Results: The AChE activity was significantly decreased and the content of neurotransmitter acetylcholine (ACh) was significantly increased in normal mice cortex and hippocampus by treatment with donepezil at dosage of 8 mg/kg, EXT at dosages of 183, 550, 1650 mg/kg and ALK at dosages of 10, 30, 90 mg/kg ( P <0.05), and the AChE activity and the content of ACh were not significantly changed in cortex and hippocampus after treatment with FLA at dosages of 10, 30, 90 mg/kg ( P >0.05). In the MWM task, scopolamine-induced a decrease in both the swimming time within the target zone and the number of crossings where the platform had been placed were significantly reversed by treatment with EXT at dosages of 550, 1650 mg/kg and ALK at dosages of 30, 90 mg/kg ( P <0.05). Moreover, the activity and protein expression of AChE was significantly decreased and the content of neurotransmitter ACh was significantly increased in cerebral cortex of scopolamine-induced mice by treatment with EXT at dosages of 183, 550, 1650 mg/kg and ALK at dosages of 10, 30, 90 mg/kg ( P <0.05), compared with scopolamine-treated group. Conclusions: EXT and ALK from APP exert beneficial effect on learning and memory processes in mice with scopolamine-induced memory impairment. APP is an effective traditional folk medicine and the ALK fraction is proved to be the main effective components for the treatment of forgetfulness. The ALK may be valuable source for lead compounds discovery and drug development for treatment of memory impairment such as in Alzheimer's disease. Graphical abstract: